Stress-strain response of the LEAP-2015 centrifuge tests and numerical predictions. Issue 113 (October 2018) - Zeghal, Mourad; Goswami, Nithyagopal; Kutter, Bruce L.; Manzari, Majid T.; Abdoun, Tarek; Arduino, Pedro; Armstrong, Richard; Beaty, Michael; Chen, Yun-Min; Ghofrani, Alborz; Haigh, Stuart; Hung, Wen-Yi; et al.
Abstract: The Liquefaction Experiments and Analysis Projects (LEAP) is an international effort to produce a set of high quality test data and to then use it in a validation exercise of existing computational models and simulation procedures for soil liquefaction analysis. A validation effort (LEAP-GWU 2015) was undertaken using a benchmark centrifuge model of a sloping deposit tested in a rigid-wall container. This article presents and discusses the shear stress-strain responses and effective stress paths of the LEAP-GW 2015 centrifuge tests and numerical predictions (including an assessment of the effects of the rigid boundaries). Abstract : Highlights: Stress-strain responses of centrifuge sloping sandy deposits were analyzed. Stress-strain responses of associated numerical predictions were analyzed. The effects of rigid boundaries on soil response were assessed.